Improving Student Learning Outcomes on the Material Believing in the Books of Allah through the Project Based Learning Model at SD Negeri 0505 Hutanopan - Harahap, Irma Suryani; Hasibuan, Nur Beit (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using project based learning. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that project based learning can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.71%, the first cycle 67.39% and in the second cycle it increased to 95.96%. Thus, the use of project based learning can be used as an alternative to improve student learning outcomes in Islamic religious education learning